Reinventing social security worldwide : back to essentials / Vladimir Rys. - Rys, Vladimir (Policy Press, 2010)
In this timely book, the author, with his life-long experience of international social security, advocates reinstating social insurance by reducing the volume of income redistribution, increasing the transparency of money flows and improving citizen information.